Parents's Role in Improving Numeracy Literacy of Elementary School Students through Mathematics Competitions - Safitri, Rosalinda; Lanya, Harfin; Nurillah, Nurillah; Khoir , Alfian; Zayyadi, Moh (Universitas Islam Jember, 2025)
Mathematical numeracy literacy ability is a very important ability for students to have, because this ability is related to problem-solving both in the field of education and in everyday life. The development that occurs in early childhood can be influenced by several factors such as family, school, and environmental factors. This article was written to describe the important role of parents in increasing students' numeracy literacy in mathematics competitions. This research was conducted in Pamekasan with a qualitative research type with a descriptive approach, and the subjects in this research were elementary school students participating in Sigma 2023. The results in this research can be seen from the percentage of parents' role in increasing the numeracy literacy of elementary school students which is in the good criteria with a percentage of 79.08. Therefore, parents need to be actively involved in their children's education and provide an environment that supports their children's development so that their children's numeracy literacy skills develop as expected. Keywords: Role of Parents, Numeracy Literacy